2021
DOI: 10.1017/jfm.2021.582
|View full text |Cite
|
Sign up to set email alerts
|

Inertial effects on the flow near a moving contact line

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, one must be careful with the steady state advancing contact lines for dense fluids such as water. In those cases, the contact line capillary number might be of order one and inertial effects would play a role therefore altering the stream function solution even at the scales of a few hundred nanometres as shown in [16]. In that case, the Cox region is absent and the inner region of the Stokes flow solutions with slip models we obtained should be matched to the first-order inertially corrected Stokes flow with the no-slip boundary condition.…”
Section: A Note On Asymptotic Matching To the Far-field Solutionmentioning
confidence: 84%
“…However, one must be careful with the steady state advancing contact lines for dense fluids such as water. In those cases, the contact line capillary number might be of order one and inertial effects would play a role therefore altering the stream function solution even at the scales of a few hundred nanometres as shown in [16]. In that case, the Cox region is absent and the inner region of the Stokes flow solutions with slip models we obtained should be matched to the first-order inertially corrected Stokes flow with the no-slip boundary condition.…”
Section: A Note On Asymptotic Matching To the Far-field Solutionmentioning
confidence: 84%
“…The largest stable at exhibits oscillations similar to the so-called ‘stick-slip’ behaviour (Orejon, Sefiane & Shanahan 2011; Varma, Roy & Puthenveettil 2021). For a prolonged time, the contact line shows more resistance towards movement (i.e.…”
Section: Molecular Dynamics Simulations Of the Sheared Dropletmentioning
confidence: 94%
“…Instead, these may excite oscillation modes of the whole interface. Stick-slip has been theorized for flat surfaces and homogeneous fluids under some flow conditions (Hocking 2001;Eggers 2005;Varma et al 2021). However, to the best of the authors' knowledge, it has not been observed directly.…”
Section: Stick-slip Like Oscillationsmentioning
confidence: 99%
“…Recent work seeks to extend the description of capillary-driven flows to scenarios where gas-liquid interfaces are dominated by inertial forces Varma et al (2021); Fiorini et al (2022Fiorini et al ( , 2023c. These investigations highlight the impact of the flow further away from the contact line on the interface shape and its motion.…”
Section: Introductionmentioning
confidence: 99%